Aspect—conditioned word order alternations in Bangime - (:unkn) unknown (My University, 2024)
Bangime (ISO 639-3: dba) is a language isolate spoken in the otherwise Dogon-inhabited Bandiagara Escarpment in central-eastern Mali. Bangime data come from elicitation sessions and text collection gathered during our fieldwork in Mali from 2008-2010 and in Burkina Faso from 2011-2013 and the summer of 2023.Bangime word order depends on the TAM of the clause. Here, we concentrate on perfective-imperfective word order distinctions. The perfective aspect is object-final whereas the imperfective is verb-final. Pronouns and ‘agreement’ markers precede verbs and tense/aspect/mood ‘auxiliaries’. We use the terms ‘agreement’ and ‘auxiliary’ tentatively as these markers from part of our ongoing analysis of the language’s morpho-syntax. Examples illustrating these properties of the language are given in (1)-(2).(1) Perfective aspectS V Oɲ́=ɥàà bḭ̄ḭ̀ 3S buy.PFV goat’He bought a goat.’(2) Imperfective aspectS AUX O Vń=dà bḭ̄ḭ̀ ŋ̄=ɥáá3S IPFV goat LINK buy’He is buying a goat.’In Bangime, a subject may be expressed by a NP or a pronoun. The third person pronoun, as shown in (1)-(2) is a homorganic nasal that occurs in clause-initial position. This nasal reappears in (2) preceding the verb and appears to agree with the subject. The simple perfective as shown in (1) is unmarked save for tone on the verb and SVO word order. The imperfective is expressed by an imperfective marker that agrees with the subject in its tonal marking. The imperfective aspect further differs from the perfective in that the object precedes the verb. The aspect-conditioned word order in Bangime is, to our knowledge, unique in the zone in which Bangime is spoken. Strikingly similar patterns are found in Kwa languages spoken along the coast of the horn of West Africa in Benin. Examples (3)-(4) are drawn from Gungbe, cf. Aboh (2001: 194). However, a contact scenario between Bangime speakers and those of Gungbe would be difficult to imagine g
Keywords: African Research